From Life to Its Online School: An Analysis of Alain de Botton’s ‘The School of Life’ as Strategy and Tactic - Gökçen Karanfil; A. Özgür Gürsoy (Türkiye İletişim Araştırmaları Dergisi)
Through a critical engagement with the literature on the conceptualizations of culture, this article focuses on the possibilities for empowerment and social agency that may be found in manifestations of everyday popular culture and the critiques of this approach that voice their oppressive nature. The article draws on Michel de Certeau’s distinction between strategies and tactics, as qualified by Michel Foucault’s use of the same conceptual pair, in order to develop a conceptual grid that emphasizes their imbrication or mutual conditioning. The key advantage offered by this grid is that it makes visible the inherently ambivalent nature of cultural products and the way in which constraining strategies and liberating tactical reversals are both made possible on the same shared site. It thus argues that popular cultural works may subvert the manipulative imperatives of the culture industry only from within a strategically structured social field. It thereby becomes possible to acknowledge the insights of the culture industry perspective of critical theory, while providing a more nuanced interpretation and evaluation of certain works of popular culture. The conceptual analysis is then applied to The School of Life (an online educational organization initiated by the popular author, philosopher, and entrepreneur Alain de Botton) both to offer an examination of this cultural artifact and to test the assumptions the theoretical framework developed.